2020
DOI: 10.1038/s41598-020-61899-y
|View full text |Cite
|
Sign up to set email alerts
|

Probing and predicting ganglion cell responses to smooth electrical stimulation in healthy and blind mouse retina

Abstract: Retinal implants are used to replace lost photoreceptors in blind patients suffering from retinopathies such as retinitis pigmentosa. Patients wearing implants regain some rudimentary visual function. However, it is severely limited compared to normal vision because non-physiological stimulation strategies fail to selectively activate different retinal pathways at sufficient spatial and temporal resolution. The development of improved stimulation strategies is rendered difficult by the large space of potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 81 publications
3
20
3
Order By: Relevance
“…[15][16][17] We showed that the voltage transduced by PVMs could reach the levels that would effectively activate retinal neural layers. 6,[42][43][44] The methodology is tunable in terms of layer thicknesses, and compatible with smaller pixels (down to a few micrometers). Based on the literature, 6,31 we postulate that Ti layer serves as a capacitive charge injection material.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] We showed that the voltage transduced by PVMs could reach the levels that would effectively activate retinal neural layers. 6,[42][43][44] The methodology is tunable in terms of layer thicknesses, and compatible with smaller pixels (down to a few micrometers). Based on the literature, 6,31 we postulate that Ti layer serves as a capacitive charge injection material.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be known a priori if such an EES waveform was the optimum for a given control task. Therefore, Höfling et al 215 proposed smooth white noise EES to more closely approximate the physiological signals in the retina. Desai et al 216 experimented with different square pulse EES strategies and sinusoidal EES for seizure control in rats; sinusoidal EES was not useful, whereas the effects of theta pulse EES depended on the stimulation timing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal preparation was performed using adult B6.CXB1-Pde6brd10/J ( rd10 ) mice of either sex as described previously 58 61 . The age of the rd10 mice varied between 400–430 days postnatal.…”
Section: Methodsmentioning
confidence: 99%